Ordinal Logistic Regression Model for Human Development Index: A Case Study of Provinces in The southern part of Sumatra - Suhaimi, Alus Ahmad; Novianti, Pepi; Pangesti, Riwi Dyah (LPPM-ITEBA, 2025)
Ordinal logistic regression is a statistical method used to analyze ordinal dependent variables with three or more categories. This study aims to model the Human Development Index (HDI) in the southern Sumatra region, which includes the provinces of Bengkulu, Bangka Belitung, Jambi, South Sumatra, and Lampung. HDI is categorized into three groups: low, medium, and high. The predictor variables used include Gross Regional Domestic Product (GRDP), poverty rate, access to safe drinking water, open unemployment rate (OUR), and labor force participation rate (LFPR). The analysis results indicate that three variables significantly influence HDI: the percentage of the poor population, the proportion of households with access to safe drinking water, and the open unemployment rate (OUR). This study did not conduct a spatial heterogeneity test; therefore, it is recommended that future research incorporate such a test